Network analysis of depressive and anxiety symptoms with well-being in students during the COVID-19 pandemic: a repeated cross-sectional study - Ochnik, Dominika; Rojczyk, Ewa; Choina, Zuzanna; Nowak, Hanna; Skalska, Martyna; Sroka, Maria; Stach, Aleksandra; Sudoł-Ginalska, Natalia; Wąsik, Marta; Blažková, Ivana (Scientific reports, 2024)
The university student population is particularly vulnerable to depression, which was identified during the COVID-19 pandemic. Understanding how depressive symptoms are interrelated with mental and physical health in students is essential. The aim of this study was to reveal the network of depressive and anxiety symptoms with respect to well-being (life satisfaction, physical health, physical activity, and perceived stress) during a difficult situation-the COVID-19 pandemic-at two measurement points of different pandemic severities. A repeated cross-sectional study was conducted in June 2020 (T1) (lower pandemic severity) and March 2021 (T2) (higher pandemic severity) among 592 and 1230 Czech university students, respectively. The measurements used were the PHQ-9, GAD-7, PSS-10, SWLS, self-rated physical health (SRH), and sociodemographic survey. The network analysis approach was utilized. For the significance of differences, the χ2 test, Student's t test, and ANOVA were performed. The results revealed that scale-level depression, stress, and worse SRH increased over time, whereas life satisfaction decreased. Scale-level anxiety and physical activity were stable over time. PHQ2 Sad mood was the most central and influential node at T1 and T2. PHQ9 Suicidal Ideation was closely related to other variables at T1, whereas PHQ1 Anhedonia was closely related to other variables at T2. The most influential risk factors were the PHQ-2 score and the GAD-2 score, which are associated with uncontrollable worrying, whereas life satisfaction, physical health, and physical activity were the most protective factors. It is crucial to recognize and decrease the PHQ2 score and increase life satisfaction to improve the mental health of university students.
Keywords: Cross-Sectional Studies; deprese; Pandemics; psychický stres; cvičení; SARS-CoV-2; mladiství; Česká republika; Depression; Mental Health; průzkumy a dotazníky; Universities; mužské pohlaví; studenti; COVID-19; průřezové studie; Adult; mladý dospělý; Stress, Psychological; osobní uspokojení; univerzity; Czech Republic; Young Adult; duševní zdraví; ženské pohlaví; Suicidal Ideation; Humans; úzkost; Students; Surveys and Questionnaires; Anxiety; Personal Satisfaction; Exercise; dospělí; pandemie; Female; Adolescent; sebevražedné myšlenky; lidé; Male